1993
DOI: 10.1128/aac.37.6.1329
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of clarithromycin for treatment of experimental Lyme disease in vivo

Abstract: Clarithromycin provided effective therapy against arthritis induced by Borrelia burgdorferi infection in the hamster. In vitro, clarithromycin was at least 1 log more potent than tetracycline against two isolates of B.burgdorfieri from human sources, as measured by MICs and 50%Y inhibitory concentrations. Clarithromycin was effective in preventing the onset of B. burgdoferi-induced arthritis, as determined by several parameters of paw swelling. When administered after the onset of arthritis, clarithromycin the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Similarly, for doxycycline, the MIC varies from 0.06 µg/ml to 2 µg/ml and the MBC from 0.25 µg/ml to 6.4 µg/ml [11,19,22,28,29]. Most importantly, the results of these studies are limited by the small numbers of isolates examined (from 2 to 30 strains), in contrast to investigations involving large numbers of common rapidly growing clinical isolates [11,[31][32][33], and also because susceptibility testing is rarely performed on newly isolated strains or on borreliae obtained from patients manifesting resistance to treatment. To overcome evident methodological problems and to simplify interpretation of the in vitro effectiveness of well known and newly developed antimicrobials against the B. burgdorferi s.l.…”
Section: What We Know: In Vitro Susceptibility Testing Of B Burgdorfmentioning
confidence: 88%
“…Similarly, for doxycycline, the MIC varies from 0.06 µg/ml to 2 µg/ml and the MBC from 0.25 µg/ml to 6.4 µg/ml [11,19,22,28,29]. Most importantly, the results of these studies are limited by the small numbers of isolates examined (from 2 to 30 strains), in contrast to investigations involving large numbers of common rapidly growing clinical isolates [11,[31][32][33], and also because susceptibility testing is rarely performed on newly isolated strains or on borreliae obtained from patients manifesting resistance to treatment. To overcome evident methodological problems and to simplify interpretation of the in vitro effectiveness of well known and newly developed antimicrobials against the B. burgdorferi s.l.…”
Section: What We Know: In Vitro Susceptibility Testing Of B Burgdorfmentioning
confidence: 88%
“…To supplement their data, we conducted a similar experiment using ceftriaxone (a member of third-generation of cephalosporins), erythromycin (a member of macrolides) and clarithromycin (a member of new macrolides). In most animal studies reported to date (1,5,11,15,20,21), borrelial infection was induced by the needle inoculation of cultured cells. This route of inoculation does not accurately reflect the natural infection of Borrelia species.…”
mentioning
confidence: 99%
“…Several laboratory animal models such as hamster (1,11), jird (20,21) and mouse (5,15) have been used to assess the in vivo efficacy of antibiotics against Lyme disease borreliae. Using C3H mice infected with North Fig.…”
mentioning
confidence: 99%
“… 2,3 This microorganism has been related to CMZL in a high percentage of cases in areas with endemic Lyme disease, 4 but also, although in a smaller percentage, in non‐endemic areas 3 . Moreover, B. burgdorferi responds to clarithromycin, at least under certain conditions, 5 and it is susceptible to amoxicillin, 6 both of which were used in the treatment of the patients in the report by Mandekou‐Lefaki et al . Moreover, there are cases in literature, in which cutaneous clonal proliferations related to B. burgdorferi infection, and confirmed as lymphoma at a molecular level, have been cleared by antibiotic treatment alone 3 .…”
mentioning
confidence: 99%